2019
DOI: 10.1002/mgg3.1110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNPC3 as a novel JAK2 fusion partner gene in B‐acute lymphoblastic leukemia refractory to combination therapy including ruxolitinib

Abstract: Background Hematopoietic neoplasms with chromosomal translocations involving JAK2 are rare, and most of them show myeloproliferative neoplasm‐associated features, followed by B‐acute lymphoblastic leukemia (B‐ALL). De novo B‐ALL cases with JAK2 rearrangements are suggested to be appropriately considered as BCR‐ABL1‐like B‐ALL, but its partners varied. Methods Fluorescence in situ hybridization (FISH), RNA sequencing (RNA‐Seq), whole‐genome sequencing, and reverse transcription polymerase chain reaction (RT‐PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Four of the 10 patients received combined treatments with ruxolitinib. The patient with GOLGA5-JAK2 achieved a CR with high dose ruxolitinib (40 mg/m 2 , bid) ( 18 ), while neither the patient with RNPC3-JAK2 ( 19 ) nor the current one with STRBP-JAK2 responded to ruxolitinib. In our patient, ruxolitinib was administered at the standard dosage used for treatment of myeloproliferative diseases (20 mg bid), and whether she would benefit from an increased dose remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the 10 patients received combined treatments with ruxolitinib. The patient with GOLGA5-JAK2 achieved a CR with high dose ruxolitinib (40 mg/m 2 , bid) ( 18 ), while neither the patient with RNPC3-JAK2 ( 19 ) nor the current one with STRBP-JAK2 responded to ruxolitinib. In our patient, ruxolitinib was administered at the standard dosage used for treatment of myeloproliferative diseases (20 mg bid), and whether she would benefit from an increased dose remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients with a myeloid neoplasm and PCM1–JAK2 fusion gene showed a rapid initial response but relapsed after 18 and 24 months respectively 9 . A recent publication by the same group including additional patients, confirmed that responses to ruxolitinib may be transient 10 …”
Section: Figurementioning
confidence: 91%
“…Combining ruxolitinib and chemotherapy could be an alternative for patients who are unresponsive to first‐line therapy or are not eligible for allogeneic stem cell transplantation (SCT). Furthermore, ruxolitinib could be beneficial as a bridging therapy prior to allogeneic SCT, as has already been proposed in myeloid neoplasms 10,11 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations